2011
DOI: 10.1111/j.1747-0285.2011.01104.x
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Inhibition of Human Carbonic Anhydrase I and II Isozymes with Natural Phenolic Compounds

Abstract: Inhibition of two human cytosolic carbonic anhydrase (hCA, EC 4.2.1.1) isozymes I and II with some natural phenolic derivatives was investigated using the esterase assay with 4-nitrophenyl acetate as substrate. Resveratrol, catechin, silymarin, dobutamin, and curcumin showed K(I) values in the range of 4.47-9.47 mm for hCA I and of 2.86-7.44 μm against hCA II, respectively. These natural product phenols were generally competitive inhibitors with 4-nitrophenylacetate as substrate. Some natural phenols investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
125
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 179 publications
(130 citation statements)
references
References 63 publications
3
125
0
2
Order By: Relevance
“…Previously, curcumin has been shown to inhibit CA-II [9]. In this study, eight new curcumin analogs also showed to effectively inhibit CA-II at the micromolar range.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Previously, curcumin has been shown to inhibit CA-II [9]. In this study, eight new curcumin analogs also showed to effectively inhibit CA-II at the micromolar range.…”
Section: Discussionmentioning
confidence: 91%
“…Curcumin and related compounds show promising result as a molecular base on which to design novel inhibitors of CA-II [9]. Due to the amounts and the variety of curcuminoids from natural sources are limited, methods of synthesizing curcumin and its analogs have been explored [10].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is found in rodents and other higher vertebrates. Three acatalytic forms are known and called CArelated proteins (CARP) [49][50][51] . The dimeric transmembrane glycoproteins hCA IX and XII are also isoforms having an extracellular active site and are markers for a broad spectrum of hypoxic tumors [52][53][54] .…”
Section: +mentioning
confidence: 99%
“…A single band was observed for each hCA isoenzyme. Both CA isoenzymes activities were determined in accordance with the method of Verpoorte et al 77 described previously 47,49 . The increasing absorbance at 348 nm of p-nitrophenylacetate (NPA) to p-nitrophenolate (NP) was recorded during a short period (3 minutes) at 25 C using a spectrophotometer (Shimadzu, UV-VIS Spectrophotometer, UVmini-1240).…”
Section: Ca Inhibitionmentioning
confidence: 99%
“…In humans, CAs are dispersed in different tissues including the reproductive tract, the gastrointestinal tract, kidneys, the nervous system, skin, eyes, lungs, and among some others [35][36][37][38] . Carbonic anhydrase isoenzymes contain a zinc ion (Zn 2+ ) in their active site, coordinated by three His residues and a H 2 O molecule/hydroxide ion (ÀOH) in the a-and g-CAs or by two Cys and one His residues (in the b class), with the fourth ligand being a H 2 O molecule/ÀOH ion acting as nucleophile in the catalyzed reactions [39][40][41][42][43] . Cytosolic hCA I and II isoforms are spread throughout the human body and are drug targets for clinically used antiglaucoma, anticonvulsants and diuretics drugs [44][45][46][47] .…”
Section: Introductionmentioning
confidence: 99%